Too Many Calories, Refined Carbohydrates, and Saturated Fat Consumption Endow to Nonalcoholic Fatty Liver Disease in Pakistani Adults - Badder Hina Afnan, Sabhita Shabir Shaikh, Anila Rahim, Waqas Ahmed, Sahar Soomro, Areesha Khan, Ammara Abdul Majeed, Nazish Abrar, Basma Ellahi, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Nonalcoholic Fatty Liver Disease (NAFLD) is one of the leading causes of liver disease worldwide. A healthy diet plays a significant role in the prevention of NAFLD. Few studies have been done in Pakistan to evaluate the dietary intake of patients suffering from NAFLD. This study aimed to look into the dietary intake of NAFLD patients being treated at a tertiary care hospital in Karachi, Pakistan Objective: To determine the nutritional status of NAFLD patients. Method: 118 NAFLD patients, aged 18 to 60, male and female, were enrolled. Patients with advanced liver or kidney failure, decompensated liver disease, hepatocellular carcinoma, acute flare, and chronic liver disease were excluded. This cross-sectional study used an interview-administered questionnaire to collect data on sociodemographic characteristics, anthropometric measurements, nutrition-related biochemical measurements, and dietary intake (24-hour diet recall and validated food frequency questionnaire). Data were analyzed using SPSS (VERSION) Statistics v26 RESULTS: Out of 118 subjects; 69% were female, Anthropometric data revealed that 41% were morbidly obese (BMI 29 >kg/m2). The average daily calorie and protein intakes were 2135 kcal and 64.2 gm, respectively. Dietary recall indicates a high consumption of saturated fat foods including paratha (34%), cake (16.9%), pizza (17.8%), banaspati ghee (11%), and consumption of high glycemic fruits like Mango (42%) and dates (32.2%). Practical implication: this study will benefit that healthy diet plays a significant role prevention of NAFLD,and can reduce the burden of obesity and its complication in later life. Low carbohydrate intake, limiting saturated fat and increased physical activity play a vital role in management of NAFLD Conclusion: Participants with NAFLD had insufficient dietary patterns. This may be associated with lower consumption of fruits and vegetables, and increased intake of high saturated fat and glycemic index foods; behavioral strategies should be implemented to change this patient's overall dietary intake. Keywords: Non Alcoholic Fatty Liver Disease, nutritional status, dietary intake, glycemic food